PENGARUH PARAMETER WIRE CUT EDM TERHADAP LAJU PEMBUANGAN MATERIAL DAN KEAUSAN KAWAT - M Fahrur Rozy Hentihu; Dhimas Ilhamsyah; Franciscus Xaverius Kristianta; Ahmad Adib Rosyadi; Hari Arbiantara Basuki (STATOR: Jurnal Ilmiah Teknik Mesin, 2023)
To improve the performance of the WEDM process, it is necessary to adjust the WEDM parameter settings to optimize the material removal rate (MRR) by decreasing the electrode wire wear (TWR) value. Using SKD 61 steel as the material, the impact of peak current, voltage open, and wire tension on material removal rate and tool wear ratio is used to estimate the ideal level parameters. The study's findings should be able to offer suitable parameter settings for WEDM work. Peak current (Ip) of 63.7%, wire tension of 31.4%, and open voltage of up to 1.9% are the machining parameters that impact the material removal rate (MRR) in the wire cut electrical discharge machine process sequentially. Open voltage, which contributes 54.4%, the wire tension parameter, which contributes 36.5%, and the peak current (Ip) parameter, which contributes 7.8%, are the machining parameters that have the most significant cumulative influence on the tool wear ratio (TWR). Peak current parameter at level 3 (9A), open voltage parameter at level 1 (5V), and wire tension parameter at level 2 (8N) are the ideal settings for MRR and TWR, resulting in MRR values of 9.861 mm3/min and TWR as high as 0.078. The study's findings usually show that higher wire tension and peak currents enhance material removal rates because the jumps of sparks produce tremendous energy. In contrast to how to open voltage and wire tension affect the wear value of the wire, thicker wires erode more quickly because more tremendous energy is generated, necessitating ideal conditions for both responses. The results of the optimization of the two responses are produced by raising the maximum peak current, lowering the minimum open voltage, and figuring out the ideal wire tension. Keywords: Wire Cut Electrical Discharge Machine, Material Removal Rate, Tool Wear Ratio.